Covid-19 e ambienti tradizionali indù: studio di caso su salute e religione in India - Beggiora, Stefano (Salute umana e tradizioni religiose di fronte alle emergenze sanitarie, 2021)
This study proposes an analysis of the impact of the contemporary health emergency / covid-19 in traditional Hindu religious environments in India, with particular focus on the ×aṅkarācarya’s seats of the of Jhyotiṣpīṭa and Dvāraka Pīṭha. In this framework, the article highlights the perception of the emergency and related legislation during lockdowns, also emphasizing the perception of the essence of the virus in Hindu religious perspective and in particular the ways of reacting to the pandemic threat.